USER SATISFACTION ANALYSIS OF GOJEK APPLICATION USING END-USER COMPUTING SATISFACTION (EUCS) - Aura Wihati Dienislami; Aviarini Indrati (International Journal Science and Technology, 2023)
At the first time, Gojek application is the online transportation services, but now it has various services. Online transportation services in the Gojek application are GoRide and GoCar. Analysis of application performance can be done to determine the user satisfaction. The aim of this research is to analyze the Gojek application user of satisfaction, especially GoRide and GoCar online transportation services. This research consists of 3 steps. The steps are making research model and adopting questionnaire, validity and realibility test and data analysis. Evaluation is done using 5 dimensions of End User Computing Satisfaction (EUCS). It consists of content, accuracy, format, easy of use and timeliness. In addition, the demographic factors of the respondents were also added, namely gender, age and occupation. There are 100 respondents in this research. The result of this research are the user satisfaction of Gojek application, especially GoRide and GoCar, can be categorized as very satisfied. The dimensions of EUCS and demographic factors have positive affect to user satisfaction. Gojek application can develop by increasing the accuracy of information and timeliness.